Dampak Dan Perlindungan Terhadap Fenomena Kasus Pemerkosaan - Ila Adila Pramestya Putri (Hakim, 2023)
Crime cases in Indonesia occur anywhere and anytime, the increasingly widespread crime case is the phenomenon of rape. Rape is an attack of sexual intercourse which is mostly carried out by men against women, therefore, acts of rape that are warmly discussed in society are mostly women who become victims. The background of the writing of this journal is the many rape cases that have occurred in Indonesia, one of which is the case of rape in a boarding school to be precise in Bandung, with the victim being 12 female students who were carried out by the leader of the pesantren, namely the defendant Herry Wirawan. From this case, it certainly has a very detrimental impact on the victim, especially since the victim is still a teenager and has a long future. The occurrence of these phenomena must have an impact on the physical and psychological. As a result of this phenomenon, the victim becomes inferior and even afraid to socialize with the surrounding community because of the history that has been done. Even though the crime of rape is clear and the threat is regulated in Article 285 of the Criminal Code.